Cariprazine augmentation of clozapine in schizophrenia—a retrospective chart review - Siwek, Marcin; Chrobak, Adrian Andrzej; Gorostowicz, Aleksandra; Król, Patrycja; Dudek, Dominika (Frontiers in Pharmacology, 2024)
The aim of our study was to evaluate the efficacy of cariprazine augmentation of clozapine in treatment-resistant schizophrenia in a retrospective chart review. Among 916 medical records of schizophrenia patients we have identified 12 individuals treated with the combination of those drugs for the duration of 3-60 weeks (median 32 (10-40)). Clinical Global Impression Improvement (CGI-I) scores were used to measure the treatment response between the introduction of cariprazine augmentation of clozapine and the last point of the observation. Majority of patients presented treatment response (9/12 patients, 75%) after 4-16 weeks of therapy (median 6 (4-12)). Treatment was associated the decrease of positive, negative, affective and anxiety symptoms severity as well as with improvement of patients global functioning. One patient discontinued the treatment due to the side effects (akathisia) and two stopped the therapy due to the exacerbation of psychotic symptoms. Our study presents the thorough clinical description of the largest number of treatment resistant schizophrenia patients medicated with the use of cariprazine augmentation of clozapine in a "real world" setting. Our results suggest that the use of this combination may lead to the improvement in a broad range of symptoms of patients with this condition.